Genetic influences on peripheral blood cell counts: a study in baboons - Mahaney, Michael C. (The American Society of Hematology, 2005)
Interperson differences in peripheral blood cell counts in healthy individuals result from genetic and environmental influences. We used multivariate genetic analyses to assess the relative impact of genes and environment on baseline blood cell counts and indices using a pedigreed colony of baboons, an animal with well-documented analogies to human blood physiology. After accounting for age, sex, and weight, we found that genetic influences explain a significant proportion of the remaining variability, ranging from a low of 13.7% for mean corpuscular hemoglobin concentration (MCHC) to a high of 72.4% for red blood cell (RBC) number. Genes influence 38.5% of the variation in baseline white blood cell (WBC) count, a characteristic that correlates with mortality in both the general human population and clinically defined subgroups such as individuals with sickle-cell disease. We examined the interaction between pairs of traits and identified those that share common genetic influences (pleiotropy). We unexpectedly observed that the same gene or group of genes influences both WBC count and mean platelet volume (MPV). We anticipate that this approach will ultimately lead to discovery of novel insights into the biology of related traits, and ultimately identify important genes that affect hematopoiesis.